INOVASI SUSU SEGAR MENJADI ES KRIM BUAH: INOVASI DAN PEMBERDAYAAN KOMUNITAS - I Gede Arta Jaya Wididana; Ni Putu Budiadnyani (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2024)
This community service project aims to empower young entrepreneurs from the Entrepreneurship SME of Universitas Pendidikan Nasional in developing fruit-flavored ice cream made from fresh milk. Through stages of preparation, implementation, and monitoring, this activity provides training on raw material selection, production techniques, branding, financial management, and digital marketing. Results show that participants gained knowledge and skills to professionally manage an ice cream business, focusing on product innovation and sustainability. This initiative has the potential to boost the local economy and promote sustainable business practices.